Dada a função f(x) = -x2 + 2.x – 1, determine as raízes reais.
x’ = -1
x’ = 1
x’ = 2
x’ = 3
x’ = 0
Soluções para a tarefa
Respondido por
1
-x²+2x-1 = 0 então temos
a = -1
b = 2
c = -1
![\frac{-b+- \sqrt{ b^{2} -4.a.c}}{2.a} = \frac{-2+- \sqrt{ 2^{2} -4.(-1).(-1)}}{2.(-1)} =\frac{-2+- \sqrt{4 -4}}{-2} =\frac{-2+- \sqrt{0}}{-2} \frac{-b+- \sqrt{ b^{2} -4.a.c}}{2.a} = \frac{-2+- \sqrt{ 2^{2} -4.(-1).(-1)}}{2.(-1)} =\frac{-2+- \sqrt{4 -4}}{-2} =\frac{-2+- \sqrt{0}}{-2}](https://tex.z-dn.net/?f=++%5Cfrac%7B-b%2B-+%5Csqrt%7B+b%5E%7B2%7D+-4.a.c%7D%7D%7B2.a%7D++%3D+++%5Cfrac%7B-2%2B-+%5Csqrt%7B+2%5E%7B2%7D+-4.%28-1%29.%28-1%29%7D%7D%7B2.%28-1%29%7D+%3D%5Cfrac%7B-2%2B-+%5Csqrt%7B4+-4%7D%7D%7B-2%7D+%3D%5Cfrac%7B-2%2B-+%5Csqrt%7B0%7D%7D%7B-2%7D)
x' =
a = -1
b = 2
c = -1
x' =
Perguntas interessantes
Matemática,
11 meses atrás
Biologia,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás